Initial Study of Heavy Metals’ Absorbability of some Aquatic Plants in the Water of West Lake - Hanoi - Huong, Luu Thi Lan; Hoa, Bui Thi (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 1S, 2016)
Abstract: In this study we have used 5 plant spieces (water lettuce - Pistia stratiotes , water hyacinth - Eichhornia crassipes , duckweed - spirodela polyrhiza , azolla - Azolla caroliniana and umbrella  sedge - Cyperus involucratus ) that were cultured in West lake’ water, to explore the capability of absorbing heavy metals of these plants. Research results show that all plants are capable of absorbing heavy metals. Because of metals absorbability, the plants can reduce the content of heavy metals in the aquaculture water after experiments compared to that of the before  experiments (the content of As decreased from 37% to 3%, Pb from 76% to 18%, Cd from 75% to 12 % and Hg from 46% to 8%) and the corresponding metal content in their bodies increases (the concentration of As increased from 147% to 15%, Cd from 67% to 20%, Pb from 152% to 41%, Hg increased a little). The result after one month shows that: These plants have good capability of absorbing As and Pb, poor capability of absorbing Cd and Hg. Umbrella sedge has the best absorbability of metals, followed by water hyacinth, water lettuce and duckweed. The absorbability of azolla is the least among plants species chosen for experiments. Keywords: Aquatic plant, heavy metals, West lake, heavy metal absorbability.